Privacy Concerns in Digital Journalism: Balancing Transparency and Ethical Reporting - Moehammad Iqbal Sultan; Andi Subhan Amir (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
This study investigates the ethical dimensions of digital journalism with a focus on privacy, aiming to shed light on the challenges faced by journalists in balancing transparency with the protection of individual privacy rights. A qualitative analysis was conducted, incorporating case studies and an examination of legal frameworks to understand the ethical dilemmas digital journalists encounter. Additionally, established best practices were analyzed to ascertain effective strategies for addressing privacy concerns. The study revealed that journalists encounter multifaceted ethical challenges when handling personal information. Case studies underscored instances where inadequate privacy considerations led to real-world harm. Legal frameworks, including GDPR and COPPA, impose responsibilities on journalists to responsibly handle personal data. In conclusion, this study underscores the critical role of ethical reporting in the digital journalism landscape. By prioritizing privacy considerations, journalists can navigate the complex landscape, ensuring that their work upholds both journalistic integrity and individual privacy rights.